The Plasminogen (Fibrinolytic) System - Collen, Désiré (Thrombosis and Haemostasis, 1999)
The plasminogen (fibrinolytic) system (Fig. 1) comprises an inactive proenzyme, plasminogen, that can be converted to the active enzyme, plasmin. Plasmin degrades fibrin and activates matrix metalloproteinases (MMPs) that, in turn, degrade the extracellular matrix (ECM).1-3 Two physiological plasminogen activators (PAs) have been identified: tissue-type PA (t-PA) and urokinase-type PA (u-PA), which binds to a cellular u-PA receptor (u-PAR). Inhibition of the plasminogen/MMP system occurs at the level of the PA, by specific PA inhibitors (PAIs), at the level of plasmin, primarily by α2-antiplasmin, or at the level of MMPs, by tissue inhibitors of MMPs (TIMPs).The dual roles of the plasminogen system are presently well established. The t-PA-mediated pathway is primarily involved in fibrin homeostasis, and the u-PA-mediated pathway is primarily involved in phenomena, such as cell migration and tissue remodeling. Consequently, the terminology “fibrinolytic system” has become inadequate and, therefore, will be replaced by “plasminogen system” in the present review.In 1980, the state of knowledge concerning the plasminogen system was summarized.4 At that time, most of the components of the system (except the PAIs) were identified and biochemically characterized (except t-PA), but thrombolytic therapy was still in its infancy. The pathophysiologic role of the plasminogen system was deduced indirectly from correlations between levels of its components and clinical disease states, whereas its role in vascular biology, matrix remodeling, tumor growth and dissemination, wound healing, and infection was largely unknown. The last 20 years have witnessed a rapidly progressing elucidation of the biochemistry, (patho)physiology, and therapeutic applications of the plasminogen system. This development has been catalyzed by the emergence of powerful molecular biological technologies, including recombinant DNA techniques for the expression of heterologous proteins and targeted gene manipulation in vivo for the elucidation of the (patho)physiological role of their translation products.The aim of the present review is to summarize the main developments in the plasminogen field since the 1980s. This account will be incomplete, since references to much significant work were omitted due to space limitations. To alleviate this shortcoming, reference is made primarily to review articles, in which more details and citations to original work can be found.